Breaking into Transgender Life: Transgender Audiences' Experiences with "First of Its Kind" Visibility in Popular Media. (8th February 2017) - Cavalcante, Andre
Abstract: Drawing from ethnographic fieldwork with transgender individuals and communities, this article explores transgender audiences' interactions with what I call "breakout texts, " media that portray "first of its kind" representation. I analyze the films Boys Don't Cry (1999) and TransAmerica (2005) as transgender breakout texts, or media that break into the cultural mainstream, break with historical representational paradigms, and break into the everyday life of viewers. Focusing mainly on this last break, I examine how transgender audiences discern breakout texts through a paradigm of mediatized "linked fate" (Dawson, 1994); how audiences move from "cultural readers" (Bobo, 1988) to cultural interpreters as a result of breakout texts' cultural popularity; and how audiences engage in "queer identity work" (Gray, 2009) with breakout texts .